ANALYSIS OF SPEAKING ANXIETY AMONG EFL LEARNERS (International journal of artificial intelligence, 2026)
This article investigates the phenomenon of speaking anxiety among EFL (English as a Foreign Language) learners and analyzes its psychological, pedagogical, and linguistic dimensions within the framework of foreign language acquisition. Speaking anxiety has become one of the most significant barriers preventing learners from achieving communicative competence in English language classrooms. Statistical data obtained from questionnaires, classroom observations, and semi-structured interviews reveal that fear of negative evaluation, lack of self-confidence, insufficient vocabulary, and teacher-centered instruction significantly contribute to learners’ oral communication anxiety. The findings also indicate that anxiety negatively affects learners’ fluency, pronunciation, classroom participation, and overall academic performance. Furthermore, the study demonstrates that interactive teaching strategies and supportive classroom environments reduce anxiety levels and improve speaking performance. Based on the results, several pedagogical recommendations and directions for future research are proposed.